Respectful Treatment of Women in Midwife Obstetric Units: An Interventional Study to Improve Clinical Care in Tshwane District, South Africa - Pattinson, Robert C (University of Pretoria, 2026)
Thesis (PhD Family Medicine)--Univeristy of Pretoria, 2019